Changes in osmoregulatory metabolism of cotton genotypes during water deficit and recovery period - Macêdo,Érika C. F. de (2019)
ABSTRACT The aim of this study was to evaluate the changes in osmoregulatory metabolism of cotton genotypes subjected to water deficit and recovery period. In a greenhouse, six cotton genotypes and two water managements were combined in a 6 x 2 factorial scheme, in a completely randomized design, evaluated after 14 and 22 days under water stress and recovery conditions, respectively. The water status, growth indicators and compatible solutes in the leaves were evaluated. The genotypes BRS Seridó, BRS Aroeira and BRS 7MH withstand better the stress condition because they had lower variations in their water potentials due to the osmotic adjustment and maintained their growth under water deficit conditions. The BRS 286 is the most sensitive genotype to the water deficit condition, since it showed greater variations in its water potential, which ultimately stopped its growth. Water replacement during the recovery period allowed growth resumption in most of the genotypes, mainly CNPA 5M and BRS 286. After the recovery period, variations in the concentrations of osmoregulators indicate the plasticity of cotton in regulating the concentrations of osmoregulators under favorable and unfavorable water conditions.